Templating Functional Materials Using Self-Assembled Block Copolymer Thin-Film for Nanodevices - Subramanian, Ashwanth; Tiwale, Nikhil; Lee, Won-Il; Nam, Chang-Yong (Frontiers in Nanotechnology, 2021)
The nanomorphologies and nanoarchitectures that can be synthesized using block copolymer (BCP) thin-film self-assembly have inspired a variety of new applications, which offer various advantages, such as, small device footprint, low operational power and enhanced device performance. Imperative for these applications, however, is the ability to transform these small polymeric patterns into useful inorganic structures. BCP-templated inorganic nanostructures have shown the potential for use as active materials in various electronic device applications, including, field-effect transistors, photodetectors, gas sensors and many more. This article reviews various strategies that have been implemented in the past decade to fabricate devices at nanoscale using block copolymer thin films.